Teachers’ Verbal Communication Strategies in Fostering Elementary EFL Students’ Willingness to Communicate - Mia Refsi Choirunnisa; Lusi Nurhayati; Ari Purnawan; Nur Hidayanto Pancoro Setyo Putro (Universitas Hamzanwadi, 2025)
Teachers’ verbal communication plays a central role in facilitating students’ oral participation in English as a Foreign Language (EFL) classrooms, particularly at the elementary level, where learners’ linguistic resources are still developing. This qualitative descriptive study examines the verbal communication strategies an English teacher uses to stimulate and support English-speaking participation among third-grade students in an EFL classroom. The study focuses exclusively on teachers’ verbal discourse as a form of instructional and affective support for students’ oral production. The participants consisted of one English teacher and 18 third-grade students at a private elementary school in Bandar Lampung, Indonesia. Data were collected through non-participant classroom observations and semi-structured interviews with the teacher. The data were analyzed using thematic analysis. The findings reveal four main categories of verbal communication strategies: questioning, prompting, encouragement, and feedback. Questioning and prompting emerged as the most frequently used strategies, activating prior knowledge, sustaining English use, and extending students’ oral responses. Encouragement and feedback provided affective and instructional support by reducing students’ anxiety, building confidence, and clarifying linguistic expectations. Collectively, these strategies created a supportive English-speaking classroom environment that fostered students’ willingness to communicate in English. The findings highlight the pedagogical importance of purposeful verbal communication strategies in supporting young learners’ oral participation in EFL classrooms.